Intravitreal colistin for multidrug resistant acute endophthalmitis following Descemet‐stripping endothelial keratoplasty due toKlebsiella pneumoniae. Issue 3 (August 2016) - Taneja, Mukesh; Senthil, Sirisha; Paulose, Remya; Joseph, Joveeta; Sharma, Savitri; Dave, Vivek Pravin
Abstract : N/A: A 67‐year‐old man presented with decreased vision in the left eye over the previous 2 months. Pseudophakic bullous keratopathy was diagnosed and uneventful Descemet‐stripping endothelial keratoplasty performed. On postoperative day 1, the corrected distance visual acuity (CDVA) was light perception with high digital intraocular pressure. The donor lenticule showed edema with cellular infiltration. B‐scan ultrasonography was consistent with endophthalmitis. Donor lenticule extraction with therapeutic penetrating keratoplasty, vitreous biopsy, core vitrectomy, and intravitreal antibiotics was performed. The culture demonstrated multidrug‐resistant Klebsiella pneumoniae sensitive to colistin only. After multiple interventions for vitritis and glaucoma control, the endophthalmitis resolved. The final CDVA was 20/200. Financial Disclosure : None of the authors has a financial or proprietary interest in any material or method mentioned.